2023
DOI: 10.1097/jcn.0000000000000974
|View full text |Cite
|
Sign up to set email alerts
|

Dyadic Associations Between Burden and Depressive Symptoms Among Patients With Heart Failure and Their Caregivers

Abstract: Background Depressive symptoms are prevalent in patients with heart failure and their family caregivers. Given the interpersonal interactions between dyadic individuals with intimate relationship, it is essential to consider the dyads as a unit when exploring the factors associated with depressive symptoms in heart failure patient–caregiver dyads. Objective The aims of this study were to explore the dyadic effects of burden on depressive symptoms in hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 62 publications
(126 reference statements)
0
1
0
Order By: Relevance
“…As evidenced in a previous study conducted on heart failure patients and their caregivers, it was found that patients' symptom burden led to caregivers' depressive symptoms while caregivers' caregiving burden contributed to patients' depressive symptoms. These interdependent relationships suggest that dyadic interventions focused on reducing burden and perceived stress may be bene cial for relieving depressive symptoms in patient-caregiver dyads [44]. Future studies could consider dyadic interventions in supporting both the patient and their caregiver when transiting from hospital to home, and subsequently into the community.…”
Section: Discussionmentioning
confidence: 99%
“…As evidenced in a previous study conducted on heart failure patients and their caregivers, it was found that patients' symptom burden led to caregivers' depressive symptoms while caregivers' caregiving burden contributed to patients' depressive symptoms. These interdependent relationships suggest that dyadic interventions focused on reducing burden and perceived stress may be bene cial for relieving depressive symptoms in patient-caregiver dyads [44]. Future studies could consider dyadic interventions in supporting both the patient and their caregiver when transiting from hospital to home, and subsequently into the community.…”
Section: Discussionmentioning
confidence: 99%